Framing cooperative development: The bridging role of cultural and symbolic value between human and material resources. Issue 4 (8th August 2018) - Hale, James; Carolan, Michael
ABSTRACT: The Community Capitals Framework has been used by scholars and practitioners to both evaluate community projects and help leverage community resources. However, less work has examined the role of symbolic values in these processes. Drawing on extensive fieldwork, this research examines the relationship between value and identity frames and resource access in three food and agriculture cooperatives that aim for community improvement. We find that as cultural and symbolic power become concentrated, diverse cultural values, and the potential resources they represent, can become more difficult to enact. While sustained dialog during a frame process can help bridge diverse resources, additional resources are often needed to support such activities. Our work suggests that frames are related to resource access, that they can be in tension with each other, do not always reflect practice, and may help reorganize capitals access.